Investing in Sustainable Access to Communications : The Role of Telecom Energy Services Companies - International Finance Corporation (World Bank, Washington, DC, 2022)
The expansion of telecommunications services to unserved and underserved areas is key to reduce the digital connectivity gap. In order to do so, it is important to explore innovative and cost-efficient technologies and business models. Telecom Energy Services Company (TESCOs) offer solutions for powering and managing telecom companies’ networks in off-grid and bad-grid areas in chapter one. International Finance Corporation (IFC) is seeking to contribute to the growth and development of innovative solution providers for telecom sites located in areas with little to no access to electricity by providing insights into the growth perspectives of the TESCO market globally in chapters two and three. IFC presents a market segmentation framework based on current business models in chapter four. The report then examines the typical commercial arrangements and key drivers which influence the bankability of TESCOs in chapter five. IFC also estimates the total amount of financing needed in order to address the pressing need for connectivity in unserved and underserved areas and acts as a call to action to stakeholders in the industry and in the financing community to work towards bridging this important connectivity gap. The five sections covered in this report represent the key dimensions required to assess the investment opportunity for TESCOs.